2021
DOI: 10.13057/biodiv/d220510
|View full text |Cite
|
Sign up to set email alerts
|

The hematological profile of Barbonymus altus to evaluate water quality in the Badher Bank Conservation Area, Blitar, East Java, Indonesia

Abstract: Abstract. Hertika AMS, Supriatna, Darmawan A, Nugroho BA, Handoko AD, Qurniawatri AY, Prasetyawati RA. 2021. The hematological profile of Badher fish (Barbonymus altus) to evaluate water quality in the Badher Bank Conservation Area, Tawangrejo Village, Blitar District, East Java, Indonesia. Biodiversitas 22: 2532-2541. Badher fish (Barbonymus altus) is endemic to the Brantas River. After years presumably extinct, the Badher fish was found again in 2010 in the Brantas River, Tawangrejo Village, Binangun Sub-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…In normal fish, the number of erythrocyte cells ranges from 1,050,000 to 3,000,000 cells/mm 3 , 13 while the number of leucocyte cells ranges from 20,000-150,000 cells/mm 3 . 71 Therefore, erythrocyte levels in Gambusia affinis caught in Blitar, Surabaya, and Mojokerto can be considered low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal fish, the number of erythrocyte cells ranges from 1,050,000 to 3,000,000 cells/mm 3 , 13 while the number of leucocyte cells ranges from 20,000-150,000 cells/mm 3 . 71 Therefore, erythrocyte levels in Gambusia affinis caught in Blitar, Surabaya, and Mojokerto can be considered low.…”
Section: Resultsmentioning
confidence: 99%
“…The use of particular biomarkers for assessing environmental quality and the health of fish in degraded environments has proven to be useful and widely-used. 12 , 13 Fish are commonly employed to assess the quality of the aquatic environment and are recognized as bio-indicators of pollution. 14 , 15 Fish live in close proximity to their environment and are thus vulnerable to physical and chemical alterations to it, which may manifest in components of their blood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that Sulcospira testudinaria was present in the Cikeruh River [Lutfi et al, 2020], Code River [Hellen et al, 2020], Meru Betiri National Park [Suratno et al, 2020], Gunung Kidul [Isnaningsih and Listiawan, 2010], and the Brantas River [Febbyanto et al, 2015]. This species was used as a bioindicator for aquatic environmental health [Hertika et al, 2021], and was used to measure the results of efforts to reduce levels of organic matter in aquaculture wastewater [Lailiyah et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…These fish have long been used by the communities that live near the river as a source of animal protein (Pratama et al 2020;Valen et al 2022b), while some are used for the aquarium trade (Gani et al 2021;Ndobe et al 2022;Nurjirana et al 2022). Rivers also provide socio-economic value as they are widely used as water sources for domestic activities, tourism, agriculture, and other economic activities (Hertika et al 2021;Nurhayati et al 2021).…”
Section: Introductionmentioning
confidence: 99%